Identifikasi Senyawa Aktif Ekstrak Daun Pulutan (Urena lobata L) dengan GC-MS: Identification of Active Compound in Pulutan (Urena lobata L) Leaf extract using GC-MS - Ummu Farah Fadillah; Erliza Hambali; Muslich Muslich (Jurnal Sains dan Kesehatan, 2020)
Pulutan leaf (Urena lobata Linn) is a type of plant that has long been used by the community as a remedy for various diseases. This research was conducted to determine the components of active compounds contained in the ethanol extract of pulutan leaves using GC-MS. The identification results showed that 50% ethanol extract of the pulutan leaves contained 5 compounds dominated by carbonic acid,monoamide,N-(2-ethylphenyl)-,propyl ester, Stigmasta-3,5-diene, and n-Hexadecanoic acid. Whereas 70% ethanol extract contained 18 compounds dominated by 4h-pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl-, 2-methoxy-4-vinylphenol, phenol, 2,6- dimethoxy-, and n-hexadecanoic acid.